The Effect of Drain vs. no Drain on Straight Leg raising in post Total Knee Replacement Patients - Askari, Raza; Hashmi, Pervaiz M.; Haq, Sheikh Naeem-ul-; Zaidi, Syed Itaat Hussain (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To compare the use of drains vs. no drains in post TKR patients on the basis of mean days to achieve first straight leg raise. METHODOLOGY: This Cohort Observational Study was carried out at section of Orthopaedic, Dept of Surgery, Aga Khan University Karachi. A total of 94 patients meeting the selection criteria and giving informed consent were included in the study. Inclusion criteria: Patient having bilateral knee joint osteoarthritis grade 4. Exclusion criteria: Septic knee, any infection elsewhere in the body, patients undergoing total knee replacement due to any other cause like rheumatoid arthritis , post traumatic arthritis etc , apart from osteoarthritis. Consecutive series was used and were operated by a single orthopedic surgeon with >5 years of experience. In the first 47 patients suction drain was used while in the next 47 no drain was used. The assessment of straight leg raising (SLR) was performed by a senior physiotherapist with experience of >3 years in orthopedics physiotherapy, twice a day postoperatively, until the patient performed unassisted straight leg rise. The researcher recorded all the demographic and other relevant variables along with the outcome in the Proforma. RESULTS: The results showed significant difference in SLR, but no difference in knee society score between drain group versus no drain group. CONCLUSION: We found advantage of using drain in patients with knee replacement surgeries in terms of rehabilitation that is straight leg raising. Based on the study results and discussion of findings with previous literature, it is recommended that multicenter studies with large sample sizes, measuring multiple outcomes should be conducted in future to reach a firm conclusion regarding use of drain or not in post TKR patients.